Analysis of concrete pavement joints to predict the onset of distress - Agosto, Andrew; Rasmussen, Robert O.; Cramer, Steven (Wisconsin Highway Research Program, 2007)
This report documents the investigation of a 15-mile segment of doweled plain jointed concrete pavement located on Interstate 90/94 in Juneau and Sauk Counties in the State of Wisconsin. This section has experienced a particular mode of early deterioration that had not previously been reported on other concrete pavements in the State of Wisconsin. Coupled with the fact that these pavements were less than ten years old, an investigation was conducted to seek out the causes of the observed distress. Three primary objectives guided the work in this effort. The first was to investigate the nature of the distress using advanced analytical methods including finite-element methods (FEM), validating the predictions using field observations when possible. The second objective was to identify maintenance and/or restoration activities that can be used to slow or prevent the propagation of the observed pavement distresses. Finally, current WisDOT design standards and specifications were reviewed to determine if previous changes made are likely to address the causes of the premature failure.
62 p.
Keywords: Pavement distress; Dowels (Fasteners); Pavement joints; Pavement maintenance; Concrete pavements; Finite element method; Unreinforced concrete; Deterioration; Rehabilitation (Maintenance); Pavement design; Wisconsin; Field studies